FAKTOR â FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN BANK KONVENSIONAL PADA BURSA EFEK INDONESIA - Ovami, Debbi Chyntia (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2017)
The objective of the research was to analyze the influence of the factors of capital adequacy ratio (CAR), third-party funds (DPK), non performing loan (NPL), operating expense and operating revenue (BOPO) and loan to deposit ratio (LDR) simultaneously and partially on the financial performance. The population was 41 conventional bank listed in the Indonesia Stock Exchange from 2010 to 2014, and 20 were used as the samples, using purposive sampling technique. The data were processed by using multiple linear regression tests with SPSS software program. The result of the research showed that CAR, DPK, NPL, BOPO and LDR simultaneously on the financial performance. Partially, CAR had positive and significant influence on the financial performance, BOPO had negative and significant influence on the financial performance while DPK, NPL and LDR did not have any significant influence. Keywords: CAR, DPK, NPL, BOPO, LDR